2019
DOI: 10.18632/aging.102241
|View full text |Cite
|
Sign up to set email alerts
|

Chromobox homolog 8 (CBX8) Interacts with Y-Box binding protein 1 (YBX1) to promote cellular proliferation in hepatocellular carcinoma cells

Abstract: Polycomb group (PcG) proteins have recently been identified as critical regulators in tumor initiation and development. However, the function of CBX8 in human hepatocellular carcinoma (HCC) remains largely unknown. Our study was designed to explore the biological function and clinical implication of CBX8 in HCC. We investigated the interplay between CBX8 and cell cycle through Gene Set Enrichment Analysis and western blotting. Bioinformatics tools and co-immunoprecipitation were used to explore cell cycle regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…Besides, KPNA2 has been found to interact with Chromobox 8 (CBX8) in human lung adenocarcinoma cancer cells [15]. Expression of CBX8, which is a member of the polycomb family of epigenetic transcription factors, correlates with tumorigenesis in HCC and esophageal squamous cell carcinoma [16][17][18]. Additionally, the high expression of CBX8 has been elaborated to foreshadow unsatisfactory overall survival and disease-free survival (DFS) of patients with muscle invasive BCa [19].…”
mentioning
confidence: 99%
“…Besides, KPNA2 has been found to interact with Chromobox 8 (CBX8) in human lung adenocarcinoma cancer cells [15]. Expression of CBX8, which is a member of the polycomb family of epigenetic transcription factors, correlates with tumorigenesis in HCC and esophageal squamous cell carcinoma [16][17][18]. Additionally, the high expression of CBX8 has been elaborated to foreshadow unsatisfactory overall survival and disease-free survival (DFS) of patients with muscle invasive BCa [19].…”
mentioning
confidence: 99%
“…3A). CBX8 exerts cancer-promoting effects on a variety of malignant tumors, such as liver, colon and esophageal cancer (20)(21)(22)(23)(24)(25). The WT and MUT 3'-UTR (mutated at positions 617-623) sequences of CBX8 were cloned into the pGL6-miR vector.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that, in hepatocellular carcinoma, CBX8 exhibits oncogenic activity through AKT/β-catenin activation (20,21). It has also been demonstrated to interact with Y-Box binding protein 1 (YBX1) to promote the proliferation of liver cancer cells (22). CBX8 promoted tumorigenesis and radiation tolerance of esophageal squamous cell carcinoma cells by targeting APAF1 (23).…”
Section: Discussionmentioning
confidence: 99%
“…Further research indicates that these functions of CBX8 are mainly exerted by H3K27me3's control of the transcriptional expression of bone morphogenetic protein 4 (BMP4) and regulation of Smads and mitogen-activated protein kinase (MAPK) signaling pathways. It has also been shown that CBX8 exhibits oncogenic activity by activating the Akt/β-catenin signaling pathway in HCC (9,61,62).…”
Section: Discussionmentioning
confidence: 99%